Über zweifache inhomogene Systeme von Differenzengleichungen - Truschina, L. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Трушина. О двойной неоднородной системе разностных уравненийL. Trušina. Dvilypės nehomogeninės skirtuminių lygčių sistemos klausimu